Reconsidering interiorization: Self moving across language spacetimes - Bertau, Marie-Cécile; Karsten, Andrea (New Ideas in Psychology)
Sociogenesis addresses a pervasive problem in psychology given by Cartesian dualism that assigns the mental an inner locus apart from material activity. Aligning ourselves to the ongoing critical discussions of interiorization in psychology, we explore the crucial notion of space by highlighting language as sociocultural and dialogical activity performed by other-oriented individuals. We discuss space in terms of the “language spacetime”, a symbolic, embodied formation of mutually positioned speaking and listening selves. This leads beyond the “inside-outside” container metaphor and allows for a reformulation of interiorization. Interiorization is conceptualized as a continuous series of different, though mutually related movements between self and other and self and self that lead to and are supported by specific formations in language activity: reversion, transposition, and decoupling. Along a short passage of a video-based interview, we trace the reversion of dialogical positions within the addressivity constellation of the two interlocutors, their interactive creation of a heterotopic spacetime, and the decoupling of one speaker's psychological activity from the concrete here-and-now and the present other by moving and acting into this new sphere. Interiorization appears as a movement at the border of past, present, and possible future(s).
Keywords: Interiorization; Dialogical self; Language activity; Voice; Vygotsky; Heterotopia; Video-confrontation